Maurice Denis dans la Grande Guerre - Fabienne Stahl (Revue LISA)
Maurice Denis (1870-1943) did not participate actively in the First World War, but this period inevitably brought a break in his life and in his work. Although he was found medically unfit to serve on the front line, the patriotic élan he felt led him to become involved in the war effort: he was mobilised as a railway guard in Conches (Eure) and was subsequently attached to the military administration in Evreux in 1914-1915; drawings and paintings bear witness to this confused and unsettled period for the artist. Despite having home leave for the birth of his sixth child, he remained committed to the war effort. In October 1917, he undertook a mission as an army painter; noting the devastation caused by war in several (unpublished) sketchbooks, showing a detailed and poignant vision of ruined bridges, castles, churches, etc.. When Victory was finally achieved, he devoted himself to the task of commemoration.